Negative Affect, Dietary Restriction, and Food Choice in Bulimia Nervosa - Gianini, Loren (Eat Behav, 2019)
OBJECTIVE: Negative affect is a precipitant for binge eating in bulimia nervosa (BN). The purpose of the current study was to examine the effect of negative affect on food choices on a more granular level among individuals with BN using a computerized Food Choice Task. METHOD: Individuals with BN (n=25) and healthy controls (HC, n=21) participated in a computerized Food Choice Task following negative and neutral affect inductions, across two study sessions. During the task participants rated high and low-fat food items for Healthiness and Tastiness. Individuals then made a series of choices between a neutral-rated food and high and low-fat foods and were then given a snack based upon these choices. RESULTS: Overall negative affect score increased significantly for both the BN and HC groups following the negative affect induction. The group of individuals with BN, relative to the HC group, was less likely to choose high-fat foods (z=−2.763, p=0.006), and these choices were not impacted by affect condition. Health ratings influenced food choices significantly more among individuals with BN than HC (z=2.55, p=0.01). DISCUSSION: Induction of negative affect was successful, yet was not related to an increase in proportion of high-fat food choices in the group of individuals with BN. The Food Choice Task captured dietary restriction in individuals with BN and results highlight the utility of this task as a probe to examine how the values of healthiness and tastiness impact food choice in individuals with BN.